An 'unburied corpse' : the 1798 Rebellion in fiction 1799-1898 - Shanahan, Jim (Trinity College (Dublin, Ireland). School of English, 2006)
The 1798 rebellion is arguably the most significant historical event in modern Irish history. It is an analogue not only of the contentious nature of Irish history but of the Irish historical experience itself, and its interpretation remains a controversial issue today. This thesis is concerned with novels written about the 1798 rebellion in the period 1799-1898. It argues as a general principle that these novels have a value as historical artefacts and as cultural snapshots, both of changing interpretations of 1798 and of the society that produced them. It traces the ways in which the rebellion was represented and interprets the novels within the context of their own times and as a narrative thread in the ‘matrix of memory’ of 1798. The rebellion was the most popular Irish historical topic of the nineteenth century in fiction. Traditionally, outside of a small number of canonical writers and texts, comparatively little attention has been paid to the nineteenth-century Irish novel and its writers, and this has led to a situation where the work of non-canonical novelists has been dismissed as irrelevant, unimportant or as an inferior precursor to the literature of the Irish Literary Revival. In showing that these novels have something significant to say about the 1798 rebellion, questions must inevitably be raised about the Irish literary canon itself. The earliest fiction about the rebellion, written before the advent of Walter Scott’s Waverley, tended to portray 1798 as inspired by the evil doctrines of the French Revolution, making no allowance for the particular historical circumstances of Ireland. Enlightenment writers placed varying degrees of emphasis on historical context but where a historical consciousness was evident, it manifested itself largely as a suspicion of the motivations of historians. There is also evidence in the early decades of an assertive Catholic voice, although this was broadly conservative in tone. In contrast, the 1820s saw attempts by Irish novelists to put the rebellion into an historical context, but the Scott historical model forced writers to look for resolution and compromise where there was none and highlighted the difference between the Irish and British historical experience. Catholic emancipation introduced some element of resolution into Irish history and retrospectively validated one of the key reasons for the rebellion, but it also created concern among some who were unsure what emancipation would ultimately bring. One dominant consequence of this was that writers with these concerns interrogated the novel form, rejecting the thesis of compromise put forward by both the national tale and the Scott historical novel. These concerns also allowed for the development of the ‘alternative rebellion’ strategy, where an idealised rebellion was put forward in place of the actual one. Such narratives reflected an uneasy feeling that a glorious opportunity to address the problems of Ireland had been missed in the 1790s, and it also provided an outlet for a form of eighteenth-century patriotism that survived Union and the political and social crises of the nineteenth century. By 1870 the first unapologetically nationalist accounts of 1798 had appeared in fiction and the three decades up to the centenary saw the emergence of a new orthodoxy about the rebellion. This orthodoxy assumed that the nationalist interpretation of the rebellion was correct. The main historiographical conflict evident in this period is between competing nationalist interpretations of the rebellion, which broadly reflected the tensions between the Fenians and the Catholic church. Unionist novels confirmed the existence of this new consensus by largely avoiding grand narrative accounts of the rebellion, concentrating instead on personal experience and on suggesting strategies for Ireland’s future within the Union. Presbyterian writers of this period also evinced no desire to write themselves out of the rebellion narrative, reminding readers that they were part of the Irish nation too, while also stressing that the reasons for rebellion in 1798 no longer existed. An analysis of these novels reveals them to be, if not good history, then good historical material, in that they were engaged in playing out alternative scenarios, highlighting the good and bad elements of the rebellion, and suggesting strategies for the future. Arguing that it was essentially a political genre, this thematic study demonstrates that the great strength of the Irish nineteenth-century novel was the many and various uses to which it could be put, and that the novel form itself played a vitally important role in reflecting the way that historical events like 1798 were remembered, in that it was the ideal vehicle for conjoining history, tradition and imagination into one narrative whole.
Embargo End Date: 2022-01-01
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin, 2006